Aspects of reducing the effects of vehicle-borne improvised explosive devices - Drozd, Jan; Flasar, Zdenek; Rak, Luděk (Vojnotehnički glasnik / Military Technical Courier, 2018)
The paper deals with tactical and technical contexts of attacks by vehicle-borne improvised explosive devices (VBIEDs). This type of attack is usually conducted aiming at so-called "soft targets", i.e. people who are at a certain moment  in the area of a planned attack. The objectives of these attacks can be diverse. The common denominator of attacks is usually to create damaging consequences, especially a large number of dead and injured people. This paper did not focus on the elimination of these attacks, but rather on the reduction of their consequences. Since their assumption is that a complete prevention of these attacks is impossible, the authors formulated some possible solutions, (regarding the technical parameters of the means in particular) to mitigate the consequences of attacks in different ways. Some measures and technical means to mitigate the effects on people are easier to implement while some are more complex and costly.
Keywords: vehicle-borne improvised explosive device; barrier; terrorist; protection; explosion